Efficacy and safety of Qili Qiangxin Capsule in the adjuvant treatment of ischemic cardiomyopathy with heart failure: a systematic review and meta-analysis - Yin Ziwei; Zheng Huizhen; Guo Zhihua (KeAi Communications Co., Ltd., 2023)
Objective: To evaluate the efficacy and safety of Qili Qiangxin Capsule (QLQXC) combined with western medicine in patients with ischemic cardiomyopathy (ICM) comorbid with heart failure (HF) for clinical application. Methods: We searched relevant references in Chinese databases including China National Knowledge Infrastructure (CNKI), China Scientific Journal Database (VIP), Wanfang Database, and China Biology Medicine (CBM), as well as English databases including PubMed and Embase, from the foundation of the database to January 8, 2023, without language restrictions. All statistical analyses, including subgroup and sensitivity analyses, were performed using the Review Manager (version 5.4) and Stata (version 15.0). Results: QLQXC combined with western medicine significantly increased the endpoints of overall response rate (ORR) (P < 0.000 01), left ventricular ejection fraction (LVEF) (P < 0.000 01), the score of Minnesota Living with Heart Failure Questionnaire (MLHFQ) (P = 0.000 2), and 6-minute walking distance (6MWD) (P < 0.000 01), decreased left ventricular end-diastolic diameter (LVEDD) (P < 0.000 01), left ventricular end-systolic diameter (LVESD) (P = 0.03), and pro-brain natriuretic peptide (pro-BNP) (P < 0.00001), and reduced the incidence of rehospitalization (P = 0.0003) and adverse events (AEs) (P = 0.000 6) compared with those under the conventional western therapy alone. Nonetheless, no significant difference was observed in reducing the mortality between the QLQXC combined with western medicine group and the western medicine group (P = 0.30). Conclusion: The combination therapy of QLQXC with western medicine can potentiate cardiac function and raise the quality of life in patients with ICM comorbid with HF.